Comparison of Various Concentrations of Carbol Fuchsin Solutions in Ziehl-Neelsen Staining for Detection of Acid-Fast Bacilli in Sputum Samples - Iduh, M.U.* , Spencer, T.H.I. , Mohammed, K. , Garba, M.K. , Nataala, S.U. , Ashcroft, O.F. , Abdulrashid, L. (Sokoto Journal of Medical Laboratory Science)
This study was carried out to evaluate Ziehl-Neelsen staining using various concentrations of carbol fuchsin solution. Duplicate smears from 173 sputum samples were made and stained with 1%, 0.3% and 0.1% carbol fuchsin solution. The smear results were recorded semi quantitatively according to the WHO guidelines. A comparative analysis of the results obtained from each carbol fuchsin solution was carried out the McNemar test and p-value was determined. P-value of <0.05 was considered significant. Comparison of 1% and 0.3% carbol fuchsin solution shows close relationship with McNemar chi square of 3.0 and p-value of 0.39. The agreement from these results had a kappa value of 0.934. Twenty-five (25) of the 173 samples were positive and detected by 1% and 0.3% concentrations, 25(14%) and 25(14%) respectively. Comparison of 1% and 0.1% carbol fuchsin solution indicates a very poor relationship with a McNemar of 18 and a significant p-value of 0.012. Twenty-five (25) of the 173 samples were positive which was detected by 1% 25(14%) and 0.1% detected only 20(11%). The sensitivity of ZN using 0.3% and 1% basic fuchsin was comparable, while it was reduced using 0.1% compared to 1% basic fuchsin. Reducing the concentration of basic fuchsin below 0.3% in ZN staining was found to significantly reduce its sensitivity.